Peningkatan Kematangan Karir Siswa dengan Teori Holland - Robbi Asri; Afdal Afdal; A Muri Yusuf (Indonesian Counselor Association (IKI), 2021)
This article discusses efforts to increase students' career maturity using Holland's theory where we know at this time students are difficult to determine the career choice they will go to and also because low career maturity will result in students making wrong career decisions in the future. The method used is a literature review by critically analyzing current research on a particular topic. This article also discusses about 1.) the basic concepts of Holland's theory. 2.) characteristics of Holland's theory 3.) Strengths and weaknesses of Holland's theory. 4.) career maturity. Holland's theory discusses how to choose a career based on personality type. Holland's typological theory establishes the relationship between personality and environment by categorizing between interests and personal characteristics in a combination of six types of work: RIASEC.